Terra urbana, propriedade e gentrificação na periferia: dinâmica imobiliária e capitalismo patrimonial no Vetor Norte de Belo Horizonte, Brasil, 1999 a 2019 - Ana Luiza Nabuco (2021)
This thesis has a double goal, to verify the occurrence of gentrification processes and to understand the dynamics of land tenure, in a peripheral area of Belo Horizonte´s city, which over the past 15 years has received massive public-private partnership (PPPs) investments in large-scale urban projects. This is the “North Axis of Belo Horizonte (VNBH), delimited in this research by the Administrative Regions Norte and Venda Nova. More specifically, we verify whether and how gentrification processes occur, after the implementation of large-scale urban projects (LSUP), since 2003, which aimed at transforming this area into a new centrality, attractive to international capital. Simultaneously, we seek to detail and understand possible consequences of LSUP in local land tenure’s dynamics. This research uses, in a pioneering way, data scarcely known in academic research, among which municipal land and services tax database - IPTU, ITBI and ISS - and notary data. It proposes an unprecedented methodology for its analysis, from a spatiotemporal approach and combines quantitative research and qualitative interviews and focus groups. The multiple territorial scales of analysis is central to the detection of “new build gentrification”, which takes place in vacant land or in old industrial warehouses and is concentrated in small “islands”. For that reason, “leap frog” urbanization, characteristic of the occupation of Belo Horizonte, in previous decades, seems to have created spaces for current gentrification processes, in peripheral areas of the city. This implies that gentrification in the VNBH is associated with contemporary public-private partnerships and urban entrepreneurship strategies but, also with structural aspects of the city's urban formation. Both residential and commercial gentrification processes are present. Evidence of indirect mechanisms of eviction of old residents is found and must be considered in order to understand the slow and territorially restricted character of these gentrification processes, whose future scope is uncertain. Dynamic analysis of land tenure reveals that vacant land’s tenure, which was already very concentrated before the LSUPs, in peripheral areas of the city, reaches very high levels, in the North Axis of Belo Horizonte, after public investments. The results highlight the central role in defining the use of urban land of private agents, who own the majority of vacant land. Construction, real estate and finance activities, for all the scales of analysis, possess most of the private vacant land. This concentration by the construction industry is linked to two different speculative movements. One with a more traditional format, typical of medium-sized construction companies, representative of the period before the LSUPs, named in the literature as “passive speculation” or “inductive speculation”, depending on its characteristics. It implies using land tenure as a mechanism to appropriate part of the land rent, via surplus. The second one, characteristic of the last decade, is associated with large construction companies and financialization process and implies increasing “land banks”. We have named it “financial speculation of land”: land tenure allows these enterprises to be paid interests. Even if the future scope of gentrification is uncertain in the North Axis of the city, land’s patrimonial capitalism seems to reinforce eviction processes.